Antioxidant, Anti-inflammatory and Anti-hyperglycaemic Activities of Essential Oils from Thymbra capitata, Thymus albicans, Thymus caespititius, Thymus carnosus, Thymus lotocephalus and Thymus mastichina from Portugal - S, Azza (2017)
The in vitro antioxidant, anti-inflammatory, anti-hyperglycaemic, and anti-acetylcholinesterase activities of the essential oils (EOs) isolated from six Lamiaceae species (Thymbra capitata, Thymus albicans, Th. caespititius, Th. carnosus, Th. lotocephalus and Th. mastichina) grown in Portugal, were evaluated. Th. caespititius and T. capitata carvacrol/thymol-rich EOs showed the best capacity for preventing lipid peroxidation, and scavenging the 2,2 '-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and peroxyl free radicals, as well as for inhibiting lipoxygenase and alpha-amylase. However, Th. caespititius and Th. lotocephalus 1,8-cineole and linalool rich EOs were the best inhibitors of alpha-glucosidase. T. capitata, Th. lotocephalus and Th. albicans EOs were the most active for inhibiting acetylcholinesterase. Th. caespititius and Th. mastichina EOs were the main scavengers of nitric oxide (NO) radicals. The comparison between the present data with a survey of the existing literature on the in vitro biological activities of the essential oils isolated from the same species from Portuguese origin, using other methodologies, showed some differences. For instance the use of two oxidizable substrates (egg yolk and lecithin liposomes) led to distinct results mainly for those samples with relatively low activity. In addition, the EOs capacity for scavenging peroxyl radicals was also influenced by the presence of cyclodextrins, as a synergism seemed to occur between EOs and those carbohydrates.